Characteristic study for wireless charging system - S. M. A., Motakabber; A H M., Zahirul Alam; Jamal, Nur Fadillah; Mazbahur, Rahman Khan (AlamBiblio Publishers, 2022)
Power is an essential requirement in these modern lifestyles. Electronic gadgets like cell phones, laptops, etc., need the least power to charge. The utilization of Wireless Power Transmission (WPT) has been a hot issue among researchers these days. Nowadays, the application of wiring is becoming very inconvenient since everything cannot be used as there are some limitations and dangers. Therefore, several techniques have been found to carry out the wireless charging purpose in this study. The power transmission through the air is much easier to implement, more efficiently and persistently charged without the demand of connection physically. In this paper, a comparison between the three techniques for wireless power chargers has been determined. Among these three, it is found that the utilization of inductive coupling techniques is the best way to implement the system.